Sink position analysis of energy efficiency in Wireless Sensor Network (WSN) using routing Stable Election Protocol (SEP) - Kholidiyah Masykuroh; Afifah Dwi Ramadhani; Islamianto Hudan Raharjo (JURNAL INFOTEL, 2022)
Wireless Sensor Network (WSN) is a wireless network that involves sensors in the network. The sensor node on the WSN will collect data information from the environment around the sensor. However, each sensor node has storage capacity, processing power, communication range, and battery life limitations. The use of energy consumption from these factors is the main problem because each sensor node uses its power consumption from the battery. Stable Election Protocol (SEP) is a type of routing protocol on WSN that uses the clustering method. SEP has a function to extend the time interval before the first node dies. This research was carried out on the SEP protocol with alive node parameters, total initial energy, and stability. This study indicates that on a network that uses 100 nodes with sink positions (0, 100), two nodes are still alive and several nodes that are still alive in several sink positions that use 200 nodes. For networks where there is still a lot of energy remaining in the sink position (0, 100) with the network using 100 nodes and for networks using 200 nodes, the remaining energy is mainly in the sink position (100, 100). The highest stability period is in the sink position (50, 50) for networks using 100 nodes, and for networks using 200 nodes, the highest stability period is in the sink position (100, 50).